PENGEMBANGAN MODEL PERMAINAN “TEMBAK KALENG” SEBAGAI ALTERNATIF PERMAINAN BOLA KECIL DALAM PEMBELAJARAN PENJASORKES BAGI SISWA KELAS VIII SMP (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
AbstrakPermainan “Tembak Kaleng” merupakan salah satu alternatif penyampaian pembelajaran Penjasorkes khususnya permainan bola kecil. Pengembangan model ini bertujuan menciptakan produk variasi permainan bola kecil dalam Penjasorkes. . Teknik analisis data yang digunakan adalah deskriptif persentase. Dari hasil uji ahli Penjasorkes hasil analisis produk sebesar 77,33% dengan kriteria cukup baik, hasil dari ahli pembelajaran I diperoleh hasil analisis produk sebesar 90,67% dengan kriteria baik sedangkan dari ahli pembelajaran II diperoleh hasil analisis produk sebesar 65,33% dengan kriteria sangat baik. Sedangkan dari uji coba kelompok kecil diperoleh data sebasar 81,67% dan uji coba lapangan diperoleh sebesar 90,33% dengan kriteria baik. Berdasarkan hasil itu, dapat disimpulkan model pengembangan permainan “Tembak Kaleng” dapat digunakan pada pembelajaran Penjasorkes untuk siswa kelas VIII AbstractGame “Tembak Kaleng” is one alternative learning delivery Penjasorkes especially small ball game. Development of this model aims to create product variations Penjasorkes small ball game. The method of research is developing. The procedure includes product development, including requirements analysis field observations, interviews and literature review, developed the initial product, expert evaluation and revision, testing and revision of the small group, large group and test the final product. The data was collected using observation sheets and questionnaires were obtained from the results of expert evaluation and filling questionnaires by students. The data analysis technique used is descriptive percentages. From the test results Penjasorkes expert product analysis of 77.33% with the criteria quite well, the results of expert learning I obtained the results of analysis of the product by 90.67% with good criterion II while learning from expert product analysis results obtained by 65.33% with criteria very well. While a small group of test data obtained 81.67% sebasar and field trials of 90.33% is obtained with the criteria well. Based on the results, it can be inferred model of development of the game “Tembak Kaleng” can be used in learning for students of class VIII Penjasorkes SMP. Key words: Development, Small Ball Game, “Tembak Kaleng”.